High intensity interval training with body weight: the new calisthenics? - Machado, Alexandre F.; Nunes, Rodolfo de Alkmim Moreira; Vale, Rodrigo Gomes de Souza; Rica, Roberta Luksevicius; Junior, Aylton Figueira; Bocalini, Danilo Sales (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Physical training based on body weight was practiced by the Roman military in ancient Rome. The use of old calisthenics has been reproduced with high-intensity interval training in several studies in the last years. Objective: The aim of this study is to do a review to identify the variables of calisthenics applied with high-intensity interval training method with the purpose of suggesting a strategy to apply in the training sessions. Method/Design: The search was conducted in MEDLINE, EMBASE, SciELO (Scientific Electronic Library Online), LILACS (Literatura Latino-americana e do Caribe em Ciências da Saúde [Centro Latinoamericano y del Caribe de Información en Ciencias de la Salud]), PUB MED CENTRAL, and Cochrane Central Register of Controlled Trials databases. Results: From the results, common points in the prescription of calisthenic HIIT with regard to “all out” load are observed. Conclusion: Based on the review results, it is suggested a guideline based on a single stimulus time of 30 seconds and differentiated recovery time for different practitioner profiles, as well as regarding the selection of exercises.